Engineering of Oxygen Vacancy and Electric‐Field Effect by Encapsulating Lithium Titanate in Reduced Graphene Oxide for Superior Lithium Ion Storage. Issue 10 (24th April 2019) - Meng, Tao; Li, Bo; Hu, Lei; Yang, Hao; Fan, Wenjie; Zhang, Shanqing; Liu, Peng; Li, Mingyang; Gu, Feng Long; Tong, Yexiang
Abstract: Rational design of nanostructured electrode materials is highly desired for developing high‐performance lithium‐ion batteries (LIBs). Encapsulating electrode materials in reduced graphene oxide (rGO) shows great potential for manipulation of physicochemical properties at the atomic level, promoting remarkable electrochemical properties. Here, a controllable strategy is proposed to synthesize a "pomegranate‐like" 3D rGO encapsulated lithium titanate composite (CT‐rGO@LTO). The experimental results demonstrate the enriched oxygen vacancies in LTO and the electronic interactions at the interface between LTO and rGO. Density functional theory (DFT) calculations confirm the charge redistribution in the CT‐rGO@LTO composite, establishing a strong electric field with oxygen vacancies. Furthermore, the extra active sites in rGO for Li‐ion storage are investigated via in situ Raman tests. Benefiting from the oxygen vacancies and the electric‐field effect, the CT‐rGO@LTO electrode delivers excellent cycling stability with a capacity retention of 87.1% after 1500 cycles at 5 C. Moreover, the CT‐rGO@LTO electrode is adopted to assemble a full cell with a LiCoO2 cathode, which also displays superior rate capability with capacities of 139.4 and 109.7 mA h g −1 at 0.5 and 10 C, respectively. This work provides profound insights of fabricating high‐performance electrode materials for advanced energy storage. Abstract : A controllable strategy to synthesize a "pomegranate‐like" 3D rGO encapsulated LTO composites (CT‐rGO@LTO) is applied in advanced lithium‐ion batteries. Benefiting from the oxygen vacancies and strong electric‐field created by the interface synergistic effect of LTO and rGO, the interfacial charge transfer and reaction kinetics can be accelerated, leading to superior rate capability and cycling stability of the CT‐rGO@LTO electrode.